Medicolegal Review: Perinatal Effexor Lawsuits and Legal Strategies Adverse to Prescribing Obstetric Providers - Kirsch, Nathan; Pacheco, Luis D.; Hossain, Amjad; Phelps, John Y., III (American Journal of Perinatology Reports, 2019)
Objectives This study was aimed to familiarize obstetricians with the legal environment surrounding Effexor lawsuits and emphasize the importance of documenting informed consent in the medical records when prescribing a medication that is being targeted for litigation.Study Design We used the LexisNexis legal search engine to review legal documents from Effexor-related cases and also used Google to search for Effexor-related lawsuits online, further researching these cases via publically available court records from district clerk offices. Finally, we conducted a year-by-year literature review from 1993 to 2017 to establish the history and evolution of scientific studies surrounding Effexor use during pregnancy.Results Litigation involving Effexor typically arises due to congenital cardiac birth defects in the neonate allegedly associated with maternal Effexor use in pregnancy. Medication manufacturers have employed a legal strategy termed the learned intermediary doctrine in an attempt to shift liability away from themselves and on to prescribing obstetricians. Manufacturers claim they adequately inform obstetricians of the risks and benefits of prescribing their product and it is the duty of the obstetrician to relay those risks and benefits to their patients.Conclusion To reduce the risk of liability exposure, obstetricians must adequately document informed consent in the medical records when prescribing medications to their pregnant patients.
Keywords: Effexor; pregnancy; learned intermediary; obstetric; lawsuit; liability; informed consent